Age at first calving and age of dam effect on daily gain (milking phase) and weaning weight in Brazilian water buffalo - Souza, Júlio César de; Malhado, Carlos Henrique Mendes; Ramos, Alcides de Amorim [UNESP]; Mota, Marcelo Falci; Jorge, André Mendes [UNESP]; Freitas, José Antonio de; Ferraz Filho, Paulo Bahiense; Weaber, Robert L.; Lamberson, William R. (My University, 2010)
The objectives were to evaluate age at first calving, and weight and gain in the milking phases of buffalo in Brazil, using 462 heifers at first parturition and 1,125 calves with gain during the milking phase and weaning weight (PROMEBULL program). The model included fixed effects of season, year, sex, herd, age of dam a covariate and random error. To evaluate age at first calving we used dams with age equal or less than 60 months. The model has fixed effects of month, year of dam at calving, herd and month of birth of dam. All sources of variation were significant. Buffalo show good gain in the milking phase and have potential for use in meat production. The parturitions were concentrating in the first semester of the year (84%). The Brazilian Buffalo has best growth in the summer due the high forage production and quality.